2015
DOI: 10.1159/000369300
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Necrosis Factor Superfamily Members TWEAK, TNFSF15 and Fibroblast Growth Factor-Inducible Protein 14 Are Upregulated in Proliferative Diabetic Retinopathy

Abstract: Purpose: Tumor necrosis factor-like weak inducer of apoptosis (TWEAK) and tumor necrosis factor superfamily member 15 (TNFSF15), members of the TNF superfamily, play important roles in the modulation of inflammation and neovascularization. TWEAK activity is mediated via binding to fibroblast growth factor-inducible molecule 14 (Fn14). We investigated the expression of TWEAK, Fn14 and TNFSF15 and the correlation between TWEAK levels and the levels of the inflammatory biomarker soluble intercellular adhesion mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
1
10
2
Order By: Relevance
“…TNFSF15 transfection could also inhibit the length and areas of rabbit corneal neovascularization [ 43 ]. Ahmed M. et al reported that TNFSF15 expression was significantly increased in SD rats and epiretinal membranes of PDR patients [ 44 ]. However, the regulation and function of TNFSF15 on the initiation and progression of DR remains elusive, and the interaction between TNFSF15 and VEGF are largely unclear as well.…”
Section: Introductionmentioning
confidence: 99%
“…TNFSF15 transfection could also inhibit the length and areas of rabbit corneal neovascularization [ 43 ]. Ahmed M. et al reported that TNFSF15 expression was significantly increased in SD rats and epiretinal membranes of PDR patients [ 44 ]. However, the regulation and function of TNFSF15 on the initiation and progression of DR remains elusive, and the interaction between TNFSF15 and VEGF are largely unclear as well.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the mechanisms of cell death in DR are still mostly unknown, with some studies showing apoptosis, whereas others suggest various different pathways. 39–42 In addition, as retinopathy in our new mutant mice progresses in a matter of weeks, these mice offer an excellent model for rapid testing of therapeutic agents for this group of incapacitating disorders and different time points of disease progression could be specifically targeted. 6 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that TWEAK and Fn14 are upregulated in vitreous fluids of patients with PDR (Abu El-Asrar et al, 2015). Specifically, TWEAK protein was found to be localized in vascular endothelial cells, mononuclear cells, and myofibroblasts in PDR epiretinal membranes (Abu El-Asrar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, TWEAK protein was found to be localized in vascular endothelial cells, mononuclear cells, and myofibroblasts in PDR epiretinal membranes (Abu El-Asrar et al, 2015). In addition, TWEAK was reported to be over expressed in synovial fibroblasts from patients with rheumatoid arthritis and psoriatic arthritis (van Kuijk et al, 2010).…”
Section: Discussionmentioning
confidence: 99%